Evaluation of Crude Oil's Influence on Infochemicals Signalling Released by Ulvalactuca Using Ni-Cu / Nanotitania Sensor. (2017) - Alsufyani, Taghreed; Fadlallah, Sahar A.
Abstract: Pollutions of seas and oceans by oil and crude oil are well thought-out as one of the most problems in environment. Owing to the existence of numerous types of algae in marine ecosystem, they contribute significantly to solve this problem through their ability to point out to the pollution via chemical signals so called infochemicals. Interestingly, the macroalgae Ulva spp. release glucose as an infochemical into the environment to communicate with their bacterial symbionts. Therefore, it is hypothesized that the liberation of glucose will be affected quantitatively as a result of pollution. Occurrence of glucose possibly will detect through oxidation by electrochemical sensors and thus leads to the significant impact on the detection of pollution in the environment. Greatly, ordered annealed TiO2 nanoporous structure prepared and supplied by Ni-Cu nanoparticles was successfully prepared by linear sweep voltammetry. Their morphologies and chemical composition were characterized by HR-SEM and EDS analysis. The prepared Ni-Cu/nanoporous TiO2 electrode was employed for non-enzymatic glucose detection in alkaline electrolyte and showed a promising electro-catalytic activity for glucose that liberated as infochemicals. Cyclic voltammetry of U. lactuca growth media where glucose is supposed to be released in the absence and in the presence of crude oil with different concentrations (10, 20, 30 mg/l) was investigated using a potential range from +0.2 to +0.9 with a scan rate of 50 mV s -1 in 0.1 M NaOH. The result shows one oxidation peak at 0.73 V and one reduction peak at 0.33 V ( vs. Ag/AgCl). The present study is considered as a first work combining between the infochemicals of algae and electrochemical sensors to indicate the degree of seawater pollution by crude oil under the condition used in this study. Further investigation is needed to proof the efficiency of U. lactuca as a bioindicatorand Ni-Cu/nanotitaniaas a sensor to detect the pollution in nature seawater.